Lightweight heat-insulation fireproof material and preparation method thereof

Through the gradient pore structure design of components such as nano alumina fibers and modified phosphorus-nitrogen flame retardants, the high strength, low thermal conductivity and high fire resistance of lightweight fire-resistant materials are solved, and high-performance lightweight heat-insulating fire-resistant materials are realized, suitable for high-rise buildings and industrial factories.

CN120535236APending Publication Date: 2025-08-26INNER MONGOLIA TECHN COLLEGE OF CONSTR
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510483724.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Existing lightweight fireproof materials are difficult to meet the requirements of high strength, ultra-low thermal conductivity and Class A fire protection at the same time, limiting their application in high-rise buildings and industrial factories.

Method used

Nanoalumina fibers, modified phosphorus-nitrogen flame retardants, zinc borate and silica aerogel are used to form a porous slurry with gradient pore structure through low-temperature foaming and curing technology to prepare lightweight heat-insulating and fire-resistant materials.

Benefits of technology

It has achieved high strength, ultra-low thermal conductivity and high fire resistance limits, with a density below 0.4 g/cm³, a reduced energy consumption by 60%, and has moisture-proof and electromagnetic shielding functions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a lightweight heat-insulating fireproof material and a preparation method thereof, and relates to the technical field of fireproof materials. The light heat-insulation fireproof material provided by the invention is prepared from the following components in parts by weight: 15 to 25 parts of nano aluminum oxide fiber, 10 to 20 parts of calcium silicate powder, 30 to 40 parts of modified phosphorus-nitrogen flame retardant, 5 to 8 parts of zinc borate, 5 to 10 parts of epoxy resin, 8 to 15 parts of silicon dioxide aerogel, 3 to 5 parts of expanded graphite, 1 to 2 parts of coupling agent, 0.5 to 1.5 parts of foaming agent and 0.1 to 0.5 part of dispersing agent. The fireproof material prepared by the invention simultaneously meets the requirements of high strength, ultralow heat conductivity coefficient and high fire endurance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fireproof materials, in particular to a lightweight heat-insulating fireproof material and a preparation method thereof. Background Art

[0002] Fireproofing materials refer to synthetic materials with special properties or inherently flame-retardant or high-temperature-resistant materials. They are primarily used to slow or prevent the spread of fire, protecting structural integrity and personnel safety. Fire resistance refers to a material's ability to maintain its structural integrity and functionality in the presence of high temperatures or fire. It can be used to evaluate a material's fireproofing performance. In the event of a fire, materials with high fire resistance can effectively prevent the spread of fire and minimize damage to building structures, thereby protecting life and property.

[0003] Fireproof materials are widely used in construction, decoration, equipment protection and other aspects. The fireproof materials widely used in the current construction field mainly include inorganic fireproof materials, organic fireproof materials, composite fireproof materials and fireproof coatings. Among them, inorganic fireproofing materials are represented by gypsum, calcium silicate board, expanded perlite, etc., which have the advantages of high fire resistance and non-toxicity, but have problems such as poor water resistance (such as gypsum easily softens when exposed to water) and low impact strength; organic fireproofing materials such as polyurethane foam and polystyrene are light and have good thermal insulation properties, but they are easy to release toxic gases when burned and have insufficient high temperature resistance; composite fireproofing materials such as metal fireproof panels (metal surface + flame retardant core material) and cement foam partition boards take into account both light weight and fireproofing properties through composite structures, but have defects such as high cost, complex construction (multi-layer composite is required), and insufficient interface bonding strength; fire-retardant coatings such as steel structure intumescent fire-retardant coatings form a carbonized layer through high-temperature expansion to delay the fire, but have strict requirements on construction thickness (must be accurate to the millimeter level), and are prone to cracking and falling off after long-term use.

[0004] Currently, lightweight fireproofing materials are widely used in various industrial and residential buildings, particularly in hotels, large shopping malls, KTVs, office buildings, apartments, and residential communities. These locations have high requirements for fire protection, and the use of lightweight fireproofing materials can effectively improve building safety. However, existing lightweight fireproofing materials struggle to simultaneously meet high strength (>10 MPa), ultra-low thermal conductivity (<0.1 W / m·K), and Class A fireproofing requirements, limiting their application in high-rise buildings, industrial plants, and other settings. Therefore, with the continuous advancement of construction technology and the increasing demand for safety, the research and application of lightweight fireproofing materials has become an inevitable trend. Summary of the Invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a lightweight heat-insulating fireproof material and a preparation method thereof, wherein the fireproof material simultaneously meets the requirements of high strength, ultra-low thermal conductivity and high fire resistance limit.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: A lightweight heat-insulating and fire-proof material comprises the following components by weight: 15-25 parts of nano-alumina fibers, 10-20 parts of calcium silicate powder, 30-40 parts of modified phosphorus-nitrogen flame retardant, 5-8 parts of zinc borate, 5-10 parts of epoxy resin, 8-15 parts of silica aerogel, 3-5 parts of expanded graphite, 1-2 parts of coupling agent, 0.5-1.5 parts of foaming agent, and 0.1-0.5 parts of dispersant.

[0007] Furthermore, the coupling agent is silane KH-550, the foaming agent is azodicarbonamide, and the dispersant is polycarboxylate.

[0008] Furthermore, the modified phosphorus-nitrogen flame retardant is a guanidine phosphate-silane modified flame retardant or an ammonium polyphosphate-pentaerythritol composite flame retardant.

[0009] Furthermore, the diameter of the nano-alumina fiber is 50-200 nm and the length is 1-5 μm; the particle size of the calcium silicate powder is ≤10 μm; the phosphorus content of the modified phosphorus-nitrogen flame retardant is ≥15%, and the nitrogen content is ≥10%; the epoxy value of the epoxy resin is 0.45-0.55; the pore size of the silica aerogel is 2-50 nm and the porosity is ≥90%; and the particle size of the expanded graphite is ≤100 mesh.

[0010] The present invention also provides a method for preparing the above-mentioned lightweight heat-insulating and fire-proof material, comprising the following steps: S1, raw material pretreatment: drying the nano-alumina fibers and calcium silicate powder, adding a coupling agent, and stirring evenly to form an inorganic skeleton material; mixing the silica aerogel and expanded graphite in proportion, and ultrasonically dispersing them to form a heat-insulating functional phase; S2, adding a modified phosphorus-nitrogen flame retardant, zinc borate, epoxy resin, and dispersant to a reactor, heating to 55-65°C and stirring for 28-35 minutes, then adding an inorganic skeleton material, a thermal insulation functional phase, and a foaming agent, controlling the temperature at 40-45°C for low-speed stirring and foaming, then heating to 55-60°C and stirring at high speed to expand the pores, forming a porous slurry with a gradient pore structure; S3, low temperature curing: The porous slurry is injected into the mold and cured under pressure at 150-180°C to form a board with uniform internal pores; after demoulding, a lightweight thermal insulation and fireproof material is obtained.

[0011] Furthermore, in step S1, the nano-alumina fibers and calcium silicate powder are dried at 180-220° C. for 1.8-2.2 hours, and then a coupling agent is added and stirred evenly at 150-200 rpm for 10-15 minutes; the silica aerogel and expanded graphite are mixed in proportion and ultrasonically dispersed for 18-25 minutes.

[0012] Furthermore, in step S2, the rotation speed of low-speed stirring is 100-150 rpm, and the low-speed stirring is carried out for 5-8 minutes; the rotation speed of high-speed stirring is 200-250 rpm, and the high-speed stirring is carried out for 10-12 minutes.

[0013] Furthermore, in step S3, the pressure is increased to 0.5-1 MPa and the curing is carried out for 1-2 hours.

[0014] Furthermore, the preparation method of the lightweight thermal insulation and fireproof material provided by the present invention also includes spraying a nano-silicon dioxide coating on the surface of the lightweight thermal insulation and fireproof material after demolding, with a spraying thickness of 50-100 μm, and drying at 75-85°C for 28-35 minutes after spraying.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention strengthens the inorganic skeleton and the compressive strength of the finished fireproof material by adding nano-alumina fibers. Silica aerogel and modified phosphorus-nitrogen flame retardants (guanidine phosphate-silane modified flame retardants or ammonium polyphosphate-pentaerythritol composite flame retardants) synergistically enhance the flame retardancy and thermal insulation fire resistance. The addition of zinc borate further enhances the high-temperature fire resistance through the carbonization catalysis of zinc borate. The fireproof material prepared by the present invention simultaneously meets the requirements of high strength, ultra-low thermal conductivity, and high fire resistance limit.

[0016] (2) The present invention introduces nanoporous materials such as aerogel into the fireproof material, which can reduce the thermal conductivity of the final product and improve the lightweight level, so that the density of the final product is lower than 0.4 g / cm³.

[0017] (3) In the process of preparing fireproof materials, the present invention adopts foaming and low-temperature curing (temperature below 200°C) to replace traditional high-temperature sintering (temperature above 1200°C), which can greatly reduce energy consumption; in addition, the present invention adopts low-temperature staged foaming technology, firstly foaming at low temperature under low temperature conditions, generating evenly distributed micron-level closed pores to form the skeleton of the thermal insulation layer; then heating and high-speed stirring are performed, and high-speed stirring introduces shear force to expand the pores and form interconnected pores. At the same time, inorganic skeleton materials (such as calcium silicate powder) and thermal insulation functional phases (such as silica aerogel) fill the pore gaps, and finally form a "micropore-mesopore-macropore" gradient structure, which can achieve light weight, high strength and thermal insulation of fireproof materials. DETAILED DESCRIPTION

[0018] The present invention will be further described below with reference to the following examples. The embodiments of the present invention include but are not limited to the following examples.

[0019] Example 1 This embodiment provides a lightweight thermal insulation and fireproof material comprising the following components by weight: 15 parts nano-alumina fibers, 10 parts calcium silicate powder, 30 parts guanidine phosphate-silane modified flame retardant, 5 parts zinc borate, 5 parts epoxy resin, 8 parts silica aerogel, 3 parts expanded graphite, 1 part coupling agent (silane KH-550), 0.5 parts foaming agent (azodicarbonamide), and 0.1 parts dispersant (polycarboxylate). The nano-alumina fibers have a diameter of 50-200 nm and a length of 1-5 μm; the calcium silicate powder has a particle size of ≤10 μm; the guanidine phosphate-silane modified flame retardant has a phosphorus content of ≥15% and a nitrogen content of ≥10%; the epoxy resin has an epoxy value of 0.45-0.55; the silica aerogel has a pore size of 2-50 nm and a porosity of ≥90%; and the expanded graphite has a particle size of ≤100 mesh.

[0020] The method for preparing fireproof materials using the above-mentioned component materials is as follows: S1: Raw material pretreatment Dry the nano-alumina fibers and calcium silicate powder at 180-220°C for 1.8-2.2 hours, add a coupling agent (silane KH-550), and stir in a high-speed mixer (150-200 rpm) for 10-15 minutes to form a surface-modified inorganic skeleton material; mix the silica aerogel and expanded graphite in proportion, and ultrasonically disperse them for 18-25 minutes to form a uniform thermal insulation functional phase.

[0021] S2: Matrix mixing and foaming Add modified phosphorus-nitrogen flame retardant (guanidine phosphate-silane modified flame retardant), zinc borate, epoxy resin, and dispersant to the reactor, heat to 55-65°C and stir for 28-35 minutes, then add inorganic skeleton material, thermal insulation functional phase, and foaming agent, control the temperature at 40-45°C and stir at low speed (100-150 rpm) for 5-8 minutes to foam, then heat to 55-60°C and stir at high speed (200-250 rpm) for 10-12 minutes to expand the pores and form a porous slurry with a gradient pore structure.

[0022] S3: Low temperature curing molding The porous slurry is injected into the mold and cured under pressure (0.5-1 MPa) at 150-180°C for 1-2 hours to form a plate with uniform internal pores; After demoulding, the surface is sprayed with a nano-silicon dioxide coating with a spraying thickness of 50-100 μm, and then dried at 75-85° C. for 28-35 minutes.

[0023] S4: Post-processing and assembly Cut into modular panels, process the edges with mortise and tenon structure, and the tenon tolerance is ±0.2mm; the panels are surface coated (PE protective film), and packaged for storage.

[0024] Traditional lightweight fireproofing materials consist solely of calcium silicate as the inorganic framework. In this embodiment, the addition of nano-alumina fibers further strengthens the inorganic framework, thereby enhancing the compressive strength of the finished fireproofing material. Silica aerogel and modified phosphorus-nitrogen flame retardants synergistically enhance flame retardancy and thermal insulation properties. The addition of zinc borate further enhances high-temperature fire resistance through its carbonization catalysis. Furthermore, the introduction of nanoporous materials, such as aerogel, in this embodiment can reduce the thermal conductivity of the finished product and improve its lightweighting. Testing has shown that the fireproofing material prepared in this embodiment has a density of 0.35 g / cm³, a compressive strength of 15.5 MPa, a thermal conductivity of 0.065 W / (m·K), and a fire resistance limit of 3.5 hours (according to ASTM E119).

[0025] In terms of process, this embodiment adopts foaming and low-temperature curing (<200°C) instead of traditional high-temperature sintering (>1200°C), which improves thermal insulation performance and reduces energy consumption, with energy consumption reduced by 60%; spraying a nano-silica coating on the surface after demolding can make the material surface both moisture-proof and electromagnetic shielding. In this embodiment, the shielding effectiveness is ≥30dB, 1GHz; in addition, this embodiment adopts low-temperature staged foaming technology to form a "dense outside and sparse inside" pore gradient. By observing the pore distribution with a scanning electron microscope (SEM), the outer layer micropores (10-50μm) account for 60%, the middle layer mesopores (50-100μm) account for 30%, and the internal macropores (100-200μm) account for 10%. The gradient distribution of pores can achieve light weight, high strength and thermal insulation of the fireproof material.

[0026] Example 2 This embodiment provides a lightweight thermal insulation and fireproof material, comprising the following components by weight: 25 parts nano-alumina fibers, 20 parts calcium silicate powder, 40 parts guanidine phosphate-silane modified flame retardant, 8 parts zinc borate, 10 parts epoxy resin, 15 parts silica aerogel, 5 parts expanded graphite, 2 parts coupling agent (silane KH-550), 1.5 parts foaming agent (azodicarbonamide), and 0.5 parts dispersant (polycarboxylate). The nano-alumina fibers have a diameter of 50-200 nm and a length of 1-5 μm; the calcium silicate powder has a particle size of ≤10 μm; the guanidine phosphate-silane modified flame retardant has a phosphorus content of ≥15% and a nitrogen content of ≥10%; the epoxy resin has an epoxy value of 0.5; the silica aerogel has a pore size of 2-50 nm and a porosity of 92%; and the expanded graphite has a particle size of ≤100 mesh.

[0027] The method for preparing fireproof materials using the above-mentioned component materials is as follows: S1: Raw material pretreatment Nano-alumina fibers and calcium silicate powder were dried at 220°C for 2.2 hours, a coupling agent (silane KH-550) was added, and the mixture was stirred in a high-speed mixer (200 rpm) for 15 minutes to form a surface-modified inorganic skeleton material; silica aerogel and expanded graphite were mixed in proportion and ultrasonically dispersed for 25 minutes to form a uniform thermal insulation functional phase.

[0028] S2: Matrix mixing and foaming Add modified phosphorus-nitrogen flame retardant (guanidine phosphate-silane modified flame retardant), zinc borate, epoxy resin, and dispersant to the reactor, heat to 65°C and stir for 35 minutes, then add inorganic skeleton material, thermal insulation functional phase and foaming agent, control the temperature at 45°C and stir at low speed (150 rpm) for 8 minutes to foam, then heat to 60°C and stir at high speed (250 rpm) for 12 minutes to expand the pores to form a porous slurry with a gradient pore structure.

[0029] S3: Low temperature curing molding The porous slurry was injected into the mold and cured under pressure (1 MPa) at 180°C for 1 hour to form a plate with uniform internal pores; After demoulding, the surface is sprayed with a nano-silicon dioxide coating with a spraying thickness of 100 μm, and then dried at 85° C. for 35 minutes.

[0030] S4: Post-processing and assembly Cut into modular panels, process the edges with mortise and tenon structure, and the tenon tolerance is ±0.2mm; the panels are surface coated (PE protective film), and packaged for storage.

[0031] Performance test: The fireproof material prepared in this example has a density of 0.37 g / cm³, a compressive strength of 15.8 MPa, a thermal conductivity of 0.068 W / (m·K), and a fire resistance limit of 3.5 hours (ASTM E119 standard).

[0032] Example 3 This embodiment provides a lightweight thermal insulation and fireproof material comprising the following components by weight: 20 parts nano-alumina fibers, 15 parts calcium silicate powder, 35 parts ammonium polyphosphate-pentaerythritol composite flame retardant, 6 parts zinc borate, 8 parts epoxy resin, 10 parts silica aerogel, 4 parts expanded graphite, 1.5 parts coupling agent (silane KH-550), 1.0 part foaming agent (azodicarbonamide), and 0.3 part dispersant (polycarboxylate). The nano-alumina fibers have a diameter of 50-200 nm and a length of 1-5 μm; the calcium silicate powder has a particle size of ≤10 μm; the ammonium polyphosphate-pentaerythritol composite flame retardant has a phosphorus content of ≥20% and a nitrogen content of ≥15%; the epoxy resin has an epoxy value of 0.55; the silica aerogel has a pore size of 2-50 nm and a porosity of 90%; and the expanded graphite has a particle size of ≤100 mesh.

[0033] The method for preparing fireproof materials using the above-mentioned component materials is as follows: S1: Raw material pretreatment Nano-alumina fibers and calcium silicate powder were dried at 200°C for 2.0 hours, a coupling agent (silane KH-550) was added, and the mixture was stirred in a high-speed mixer (180 rpm) for 12 minutes to form a surface-modified inorganic skeleton material. Silica aerogel and expanded graphite were mixed in proportion and ultrasonically dispersed for 22 minutes to form a uniform thermal insulation functional phase.

[0034] S2: Matrix mixing and foaming A modified phosphorus-nitrogen flame retardant (ammonium polyphosphate-pentaerythritol composite flame retardant), zinc borate, epoxy resin, and dispersant were added to a reactor, heated to 60°C and stirred for 30 minutes, then an inorganic skeleton material, a thermal insulation functional phase, and a foaming agent were added. The temperature was controlled at 42°C and stirred at a low speed (120 rpm) for 6 minutes to foam. The temperature was then raised to 58°C and stirred at a high speed (220 rpm) for 11 minutes to expand the pores and form a porous slurry with a gradient pore structure.

[0035] S3: Low temperature curing molding The porous slurry was injected into the mold and cured under pressure (0.8 MPa) at 160°C for 1.8 hours to form a plate with uniform internal pores; After demoulding, the surface is sprayed with a nano-silicon dioxide coating with a thickness of 80 μm, and then dried at 80° C. for 32 minutes.

[0036] S4: Post-processing and assembly Cut into modular panels, process the edges with mortise and tenon structure, and the tenon tolerance is ±0.2mm; the panels are surface coated (PE protective film), and packaged for storage.

[0037] Performance test: The fireproof material prepared in this example has a density of 0.35 g / cm³, a compressive strength of 15.8 MPa, a thermal conductivity of 0.059 W / (m·K), and a fire resistance limit of 3.5 hours (ASTM E119 standard).

[0038] Comparative Example 1 On the basis of Example 1, silica aerogel and zinc borate were not added, and the remaining components and preparation methods were the same as those in Example 1.

[0039] Performance test: The fireproof material prepared in this comparative example has a density of 0.41 g / cm³, a compressive strength of 15.4 MPa, a thermal conductivity of 0.14 W / (m·K), and a fire resistance limit of 2 hours.

[0040] Comparative Example 2 On the basis of Example 1, the modified phosphorus-nitrogen flame retardant and zinc borate are not added, and the remaining components and preparation method are the same as those in Example 1.

[0041] Performance test: The fireproof material prepared in this comparative example has a density of 0.38 g / cm³, a compressive strength of 15.5 MPa, a thermal conductivity of 0.15 W / (m·K), and a fire resistance limit of 1.8 hours.

[0042] Comparative Example 3 On the basis of Example 1, zinc borate is not added, and the remaining components and preparation method are the same as those in Example 1.

[0043] Performance test: The fireproof material prepared in this comparative example has a density of 0.41 g / cm³, a compressive strength of 15.2 MPa, a thermal conductivity of 0.089 W / (m·K), and a fire resistance limit of 2.5 hours.

[0044] The density of traditional calcium silicate board is 0.8-1.2g / cm³. The density of the fireproof materials prepared in Examples 1, 2 and 3 is lower than 0.4 g / cm³, indicating that the fireproof materials prepared by the present invention are lightweight fireproof materials, and the fireproof materials prepared by the method provided by the present invention have high compressive strength, low thermal conductivity and high fire resistance. In Comparative Example 1, no silica aerogel and zinc borate are added, and in Comparative Example 2, no modified phosphorus-nitrogen flame retardant and zinc borate are added. The thermal conductivity is greater than 0.1 W / (m·K), and the fire resistance is ≤2 hours, indicating that the flame retardant and thermal insulation properties of the material are poor when only silica aerogel or modified phosphorus-nitrogen flame retardant is added. In Comparative Example 3, no zinc borate is added, but silica aerogel and modified phosphorus-nitrogen flame retardant are added at the same time, and its thermal conductivity is reduced to 0.09. W / (m·K) is less than that of the fireproof materials prepared in Examples 1, 2 and 3, indicating that the addition of silica aerogel and modified phosphorus-nitrogen flame retardant can synergistically improve the flame retardancy and heat insulation performance. However, the thermal conductivity and fire resistance of Example 3 are still lower than those of the fireproof materials prepared in Examples 1, 2 and 3. This indicates that on the basis of the synergistic effect of adding silica aerogel and modified phosphorus-nitrogen flame retardant, zinc borate is added, and the carbonization catalytic effect of zinc borate can further improve the high-temperature fire resistance and greatly improve the fire resistance limit of the fireproof material.

[0045] The above embodiment is only one of the preferred implementation methods of the present invention and should not be used to limit the scope of protection of the present invention. Any changes or modifications that have no substantive meaning made to the main design concept and spirit of the present invention, as long as the technical problems solved are still consistent with the present invention, should be included in the scope of protection of the present invention.

Claims

1. A lightweight heat-insulating fireproof material, characterized in that: The invention comprises the following components by weight: 15-25 parts of nano-alumina fibers, 10-20 parts of calcium silicate powder, 30-40 parts of modified phosphorus-nitrogen flame retardant, 5-8 parts of zinc borate, 5-10 parts of epoxy resin, 8-15 parts of silica aerogel, 3-5 parts of expanded graphite, 1-2 parts of coupling agent, 0.5-1.5 parts of foaming agent and 0.1-0.5 parts of dispersant.

2. A lightweight heat-insulating and fire-proof material according to claim 1, characterized in that: The coupling agent is silane KH-550, the foaming agent is azodicarbonamide, and the dispersant is polycarboxylate.

3. A lightweight heat-insulating and fire-proof material according to claim 2, characterized in that: The modified phosphorus-nitrogen flame retardant is a guanidine phosphate-silane modified flame retardant or an ammonium polyphosphate-pentaerythritol composite flame retardant.

4. A lightweight heat-insulating and fire-proof material according to claim 2 or 3, characterized in that: The diameter of the nano-alumina fiber is 50-200nm and the length is 1-5μm; the particle size of the calcium silicate powder is ≤10μm; the phosphorus content of the modified phosphorus-nitrogen flame retardant is ≥15%, and the nitrogen content is ≥10%; the epoxy value of the epoxy resin is 0.45-0.55; the pore size of the silica aerogel is 2-50nm and the porosity is ≥90%; the particle size of the expanded graphite is ≤100 mesh.

5. The method for preparing a lightweight heat-insulating and fire-proof material according to claim 4, wherein: The steps include: S1, raw material pretreatment: drying the nano-alumina fibers and calcium silicate powder, adding a coupling agent, and stirring evenly to form an inorganic skeleton material; mixing the silica aerogel and expanded graphite in proportion, and ultrasonically dispersing them to form a heat-insulating functional phase; S2, adding a modified phosphorus-nitrogen flame retardant, zinc borate, epoxy resin, and dispersant to a reactor, heating to 55-65°C and stirring for 28-35 minutes, then adding an inorganic skeleton material, a thermal insulation functional phase, and a foaming agent, controlling the temperature at 40-45°C for low-speed stirring and foaming, then heating to 55-60°C and stirring at high speed to expand the pores, forming a porous slurry with a gradient pore structure; S3, low temperature curing: The porous slurry is injected into the mold and cured under pressure at 150-180°C to form a board with uniform internal pores; after demoulding, a lightweight thermal insulation and fireproof material is obtained.

6. The method for preparing a lightweight heat-insulating and fire-proof material according to claim 5, characterized in that: In step S1, the nano-alumina fibers and calcium silicate powder are dried at 180-220° C. for 1.8-2.2 hours, and then a coupling agent is added and stirred evenly at 150-200 rpm for 10-15 minutes. The silica aerogel and expanded graphite are mixed in proportion and ultrasonically dispersed for 18-25 minutes.

7. The method for preparing a lightweight heat-insulating and fire-proof material according to claim 6, characterized in that: In step S2, the rotation speed of low-speed stirring is 100-150 rpm, and the low-speed stirring is carried out for 5-8 minutes; the rotation speed of high-speed stirring is 200-250 rpm, and the high-speed stirring is carried out for 10-12 minutes.

8. The method for preparing a lightweight heat-insulating and fire-proof material according to claim 7, characterized in that: In step S3, the pressure is increased to 0.5-1 MPa and the solidification is carried out for 1-2 hours.

9. The method for preparing a lightweight heat-insulating and fire-proof material according to claim 8, characterized in that: The method further comprises spraying a nano-silicon dioxide coating onto the surface of the demoulding lightweight heat-insulating fireproof material, with a spraying thickness of 50-100 μm, and drying the coating at 75-85° C. for 28-35 minutes.

Citation Information

Cited By

  • Coal seam penetration and heat conduction dual functional composite material, and preparation method and application thereof

    CN122357119A

  • A dual-functional composite material for improving permeability and thermal conductivity in coal seams, its preparation method and application

    CN122357119B